Cidades mineiras na rede mercocidades: a inserção internacional de entes subnacionais - Braga, Hélcio Queiroz (2016)
The research theme developed in this thesis started to be elaborated, during my History graduation, which I did in UFMG. The conclusion work versed about the America’s southern cone. In 2005, in the exercise of high school teaching, which is developed in CEFET-MG, I presented in the Programa de Iniciação Científica Jr. scope, created by the institution, financed by FAPEMIG, the research project about the commercial relationship evolution between MERCOSUL countries, in the period of 1995-2004. This work, realized by a high school student, enrolled in the Villa Lobos school, opened several paths to entrench the knowledge about this theme. In this sense it allowed the elaboration of a research project to the Social Sciences Master, made in PUC-SP, oriented by Professor Eduardo W Vanderlei, which guided the research around the insertion in Belo Horizonte e Minas Gerais, in the institutional structure of the MERCOSUL. This work allowed to understand the region and political organization of the cities in this countries, which hold links with the MERCOSUL, which created the network MERCOCIDADES, referenced in the network EUROCIDADES organization, instituted in the European Union scope. In this way, this Doctorate research, constitutes in the development of the work developed in the Master's work and has its focus on the insertion of six cities of Minas Gerais - Belo Horizonte, Contagem, Juiz de Fora, Sabará, Uberlândia e Vespasiano, in the MERCOCIDADES network. The goal of the research, and identify the produced impacts in the political and economic fields, from the international insertion of theses municipalities. It may be determined the economic activity growth in the participating municipalities, which made important infrastructure transformations. For the metropolitan region of Belo Horizonte, still embedded by Contagem, Sabará and Vespasiano, the policies development made in conjunction with the government, meant this international process consolidation, highlighting the full utilization of the International Airport Tancredo Neves, powered by the Aduaneira Station, in its dependencies and the construction of Porto Seco, located in Betim, city on the metropolitan region. Finally, the government made operations along the federal government to duplicate the road section between Juiz de Fora e Belo Horizonte, in the perspective of overcome the distance between the two cities. In a different way, a similar process occurred in Uberlândia, which also started to host Porto Seco, consolidating its infrastructure as exporting centre. Two other measured amplified the international possibilities of Uberlândia: the expansion of its airport infrastructure, as well as, the duplication of the road section between Uberlândia and Belo Horizonte. Inside this context, it is possible to consider that the insertion process of these six cities in the MERCOCIDADES network, allows the creation of conditions to their economic and political growth and contributes to reinforcing their role in the MERCOCIDADES network, as a Common Market. Therefore, the thesis which guides this research has the assumption that network actions, of cities in countries with MERCOSUL links, represents a counterpoint to neoliberal fundamentals, which permeate this institution block, as well as a political movement to reinforce the ALADI proposition to build a Latin American Common Market, inside the capitalism milestones. This thesis strengthen itself by reading the statute which guides this network action, which it reads the guiding principles of the political acting of this organism is Cooperation and Integration, which apparently constitutes in counterpoint to the neoliberal economic and political fundamentals. Along to the elaborated thesis, three hypotheses can be formulated - the first goes in the sense of public policies elaboration, initiated by subnational entities, oriented by the integration and cooperation principles, with the goal of promoting improvement in the respective population living standards. The second hypothesis is the fact that cities develop mechanisms, to strengthen their financial, political, social and management autonomy, along national governments who dispose of greater economic power. The third hypothesis is that cooperative and integrated political action of network organized cities allows the redefinition of political-institutional role, which must be assigned to these subnational entities, in the international political field